Altered vagal and intestinal mechanosensory function in chronic unexplained dyspepsia. Issue 4 (1st April 1998) - Holtmann, G; Goebell, H; Jockenhoevel, F; Talley, N J
Abstract : Background —Abnormal visceral mechanosensory and vagal function may play a role in the development of functional gastrointestinal disorders. Aims —To assess whether vagal efferent and afferent function is linked with small intestinal mechanosensory function. Methods —In seven patients with functional dyspepsia, six patients with a history of Billroth I gastrectomy and/or vagotomy, and seven healthy controls, intestinal perception thresholds were tested by a randomised ramp distension procedure performed with a barostat device. On a separate day, an insulin hypoglycaemia test was performed to assess the plasma levels of pancreatic polypeptide (PP) in response to hypoglycaemia, as a test of efferent vagal function. Results —First perception of intestinal balloon distension occurred at significantly lower pressures in patients with functional dyspepsia (median 19.3, range 14.7–25.3 mm Hg) compared with healthy controls (median 26.0, range 21.7–43.7 mm Hg, p<0.01). Sensory thresholds were significantly lower in patients after gastrectomy (median 12.2, range 8.0–14.7 mm Hg, p<0.05 versus all others). In healthy controls and patients with functional dyspepsia, insulin hypoglycaemia significantly (p<0.001) increased plasma PP levels. However, only two out of seven patients with functional dyspepsia had a more than twofold increase in PP values whereas all healthy controls had a more than twofold increase in PP levels after insulin hypoglycaemia (p<0.05). In contrast, there was no significant PP response in the gastrectomised patients (median 2%, range −10 to +23%). PP responses and visceral sensory thresholds were significantly correlated ( r =0.65, p<0.002). Conclusions —The diminished PP response after insulin hypoglycaemia indicates disturbed efferent vagal function in a subgroup of patients with functional dyspepsia. The data also suggest that the intact vagal nerve may exert an antinociceptive visceral effect.